Strong Gravitational Lensing of Balart-Vagenas Regular Black Holes - Pervez, Akif; Ud Din, Hassan Moin; Ramdhan, Handika Satrio (Makara Journal of Science, 2026)
Gravitational lensing is an integral part of Einstein general theory of relativity. The existence of singularity in standard black holes is a hurdle for understanding the properties of black holes. The introduction of nonlinear electrodynamics (NLED) offers an intriguing possibility of constructing non-singular black hole. Gravitational lensing by the photon sphere probes the physical properties of lens objects such as black holes. This work presents a strong deflection limit analysis in a general asymptotically flat, stationary, spherically symmetric spacetime. We extend the analysis of the light deflection around the photon sphere-complete capture, and set a strong field limit that is opposite to the usual weak field limit. The deflection angle always diverges logarithmically when the minimum impact parameter is reached. We apply this general formalism to a singular Reissner-Nordström and a non-singular regular black hole. By comparing the coefficients characterizing these metric functions and observing the different collapsing objects, they are characterized by strong field limits. These coefficients are directly connected to the observables, such as the angular position and the magnification of the relativistic images. A supermassive black hole is modeled as a regular charged black hole at the galaxy's core